2015
DOI: 10.1007/s00167-015-3553-4
|View full text |Cite
|
Sign up to set email alerts
|

The effect of distal tibial rotation during high tibial osteotomy on the contact pressures in the knee and ankle joints

Abstract: Malrotation of the distal tibial fragment negates the intended effect of offloading the diseased compartment of the knee, with the contact pressures remaining similar to those of the native knee. Furthermore, malrotation leads to abnormal ankle contact pressures. Care should be taken to ensure appropriate rotational alignment of the distal tibial segment during intraoperative fixation of HTO procedures.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
24
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 22 publications
(24 citation statements)
references
References 28 publications
0
24
0
Order By: Relevance
“…We used data collected from seven cadaveric specimens during previous experiments aimed at quantifying the influence of lower‐limb alignment correction on intraarticular knee and ankle contact forces . The studies were performed with the approval of our institution's ethics committee.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…We used data collected from seven cadaveric specimens during previous experiments aimed at quantifying the influence of lower‐limb alignment correction on intraarticular knee and ankle contact forces . The studies were performed with the approval of our institution's ethics committee.…”
Section: Methodsmentioning
confidence: 99%
“…During the previously described biomechanical testing procedures, the hip, knee, and ankle joints of each cadaveric leg were imaged using fluoroscopy. Each knee was instrumented with a digital pressure mapping sensor (Tekscan, Inc, South Boston, Massachusetts).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…However, the osteotomy in that study did not reflect the actual condition of open wedge HTO because the osteotomy was performed at the tibia shaft, and fibulectomy was simultaneously performed between the proximal 2/3 and distal 1/3 of the fibula to harvest 2 cm of bone to facilitate tibial rotation. In another more recent biomechanical study, Suero et al [23] reported that fixation of the distal tibial fragment at 15˚of external rotation negated the intended beneficial effect of offloading the medial compartment in open wedge HTO. Taking the results of these two biomechanical studies together, although external rotation of the distal tibia might be less harmful to the biomechanical environment of the knee joint than internal rotation of the distal tibia, it is better to prevent distal tibial rotation even of a small magnitude.…”
Section: Correlation Coefficient P-valuementioning
confidence: 98%
“…[3,4] Tibial torsion is rotation of the proximal versus the distal articular axis in the transverse plane. Suero et al [5] found that malrotation of the distal tibia led to abnormal load distribution in the ankle joint. Considerable concern exists that malalignment of healed distal tibial fracture may result in post-traumatic arthritis of the ankle.…”
mentioning
confidence: 99%